2020
DOI: 10.3390/microorganisms8060822
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Dependent Methanol and Formaldehyde Oxidation in Methylobacterium aquaticum Strain 22A

Abstract: Lanthanides (Ln) are an essential cofactor for XoxF-type methanol dehydrogenases (MDHs) in Gram-negative methylotrophs. The Ln3+ dependency of XoxF has expanded knowledge and raised new questions in methylotrophy, including the differences in characteristics of XoxF-type MDHs, their regulation, and the methylotrophic metabolism including formaldehyde oxidation. In this study, we genetically identified one set of Ln3+- and Ca2+-dependent MDHs (XoxF1 and MxaFI), that are involved in methylotrophy, and an ExaF-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…The second group (G2), represented by the XoxF2 from strain AM1, is found mostly in clades A and C. The third group (G3) contains XoxF1 from Mb. aquaticum strain 22A, an Ln 3+ -dependent MDH that also participates in the regulation of mxaF in this strain ( Masuda et al, 2018 ; Yanpirat et al, 2020 ). This group is found distinctively in clade C members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second group (G2), represented by the XoxF2 from strain AM1, is found mostly in clades A and C. The third group (G3) contains XoxF1 from Mb. aquaticum strain 22A, an Ln 3+ -dependent MDH that also participates in the regulation of mxaF in this strain ( Masuda et al, 2018 ; Yanpirat et al, 2020 ). This group is found distinctively in clade C members.…”
Section: Resultsmentioning
confidence: 99%
“…Group 6 is found mostly in clade C1 members and contains a homolog of ExaF found in Mb. aquaticum strain 22A ( Yanpirat et al, 2020 ). Group 7 includes PQQ-ADH type 6a and is found mostly in members of clade C1.…”
Section: Resultsmentioning
confidence: 99%
“…Methylene-H 4 MPT is further converted to methenyl-H 4 MPT in the reaction catalyzed by methylene-H 4 MPT dehydrogenase and followed by several reactions leading to the formation of CO 2 [41]. A comprehensive analysis was performed to elucidate the distribution of the H 4 MPTdependent pathway among methylotrophic bacteria, where it was shown that it is present not only in α-proteobacteria that possess the serine cycle for formaldehyde assimilation but also methylotrophic γand β-proteobacteria, which assimilate formaldehyde through the RuMP cycle (Table 1, Section 3.1) [39,43,44,51,52]. The H 4 MPT-dependent formaldehyde dissimilation pathway was detected neither in Amycolatopsis methanolica nor in B. methanolicus MGA3 [39].…”
Section: Formaldehyde Dissimilatory Pathways In Native Methylotrophsmentioning
confidence: 99%
“…S-Formyl-GSH is then hydrolyzed by S-formyl-GSH hydrolase (Fgh) to GSH and formate, with the latter being subsequently oxidized to CO 2 (Figure 2) [54]. This pathway is present and functional in different α-proteobacteria, for example, Methylobacterium aquaticum 22A, P. denitrificans, Rhodobacter sphaeroides, and Rhodopseudomonas acidophila (Table 1) [40,51,54,[57][58][59][60].…”
Section: Formaldehyde Dissimilatory Pathways In Native Methylotrophsmentioning
confidence: 99%
See 1 more Smart Citation